2016
DOI: 10.1371/journal.pone.0167271
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Diabetes on the Perioperative Outcomes of Colorectal Cancer Surgery Patients

Abstract: There are approximately 1.3 million patients in Australia with diabetes. Conflicting reports exist in the literature as to the effect of diabetes on the outcomes of colorectal cancer patients. We hypothesized that patients with diabetes would have poorer perioperative outcomes, and that diabetes was an independent risk factor for both 30-day mortality and perioperative morbidity. The aim of this study was to assess the impact of diabetes on perioperative colorectal cancer surgery outcomes, as compared to a dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 18 publications
1
20
1
Order By: Relevance
“…The present study identified that 21.94% of stage I/II colon cancer patients undergoing open colectomy had comorbid diabetes in the US. The diabetes prevalence rate in our study population seems to be higher than those previously reported in New Zealand, England, and Australia (10.9% to 16.8%) [10][11][12]; however, these previous studies did not specifically focus on stage I/II colon cancer and open colectomy, so no fair comparison can be made. Furthermore, Sarfati et al [10] reported that among colon cancer patients with comorbid diabetes, 54.13% of them had uncomplicated diabetes and 45.87% had complicated diabetes, although no information about cancer stage was available in their study.…”
Section: Biomed Research Internationalcontrasting
confidence: 90%
See 1 more Smart Citation
“…The present study identified that 21.94% of stage I/II colon cancer patients undergoing open colectomy had comorbid diabetes in the US. The diabetes prevalence rate in our study population seems to be higher than those previously reported in New Zealand, England, and Australia (10.9% to 16.8%) [10][11][12]; however, these previous studies did not specifically focus on stage I/II colon cancer and open colectomy, so no fair comparison can be made. Furthermore, Sarfati et al [10] reported that among colon cancer patients with comorbid diabetes, 54.13% of them had uncomplicated diabetes and 45.87% had complicated diabetes, although no information about cancer stage was available in their study.…”
Section: Biomed Research Internationalcontrasting
confidence: 90%
“…Comorbidity is associated with adverse outcomes in colon cancer patients after surgery, and diabetes is one of the most common comorbidities [8,9]. Among colon cancer patients, the diabetes prevalence rates were 10.9%, 11.4%, and 16.8% in New Zealand, England, and Australia, respectively [10][11][12]. However, most studies that investigated the effect of comorbid diabetes on short-term surgical outcomes in colorectal cancer did not distinguish colon cancer from rectal cancer [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“… 18 , 19 It has been reported that metabolic syndrome or DM is associated with not only an increased risk for CRC 20 23 but all-cause and CRC-specific mortality. 24 27 The present study also showed the increased mortality in CRC patients with DM. However, dyslipidemia was associated with a lower mortality rate might be due to the anti-CRC properties of statin.…”
Section: Discussionsupporting
confidence: 71%
“…As we limited selection to a set of standard colon operations, our results can only be generalized to this group. We adjusted for known confounding factors, such as age and anaesthesiological risk according to ASA class, but we did not adjust for specific comorbidities such as diabetes , smoking , physical activity or alcohol misuse . Our cohort ranged over a large year span, from 2006 to 2016.…”
Section: Discussionmentioning
confidence: 99%